Integration of genome-wide association studies, metabolomics, and transcriptomics reveals phenolic acid- and flavonoid-associated genes and their regulatory elements under drought stress in rapeseed flowers - Salami, Maryam; Heidari, Bahram; Batley, Jacqueline; Wang, Jin; Tan, Xiao-Li; Richards, Christopher; Tan, Helin (Frontiers in Plant Science, 2024)
Biochemical and metabolic processes help plants tolerate the adverse effects of drought. In plants accumulating bioactive compounds, understanding the genetic control of the biosynthesis of biochemical pathways helps the discovery of candidate gene–metabolite relationships. The metabolic profile of flowers in 119 rapeseed (Brassica napus) accessions was assessed over two irrigation treatments, one a well-watered (WW) condition and the other a drought stress (DS) regime. We integrated information gained from 52,157 single nucleotide polymorphism (SNP) markers, metabolites and transcriptomes to identify linked SNPs and candidate genes responsible for the genetic control of flower phenolic compounds and regulatory elements. In genome wide association study (GWAS), of the SNPs tested 29,310 SNPs were qualified to assess population structure and linkage disequilibrium (LD) of which several SNPs for radical scavenging activity (RSA) and total flavanol content (TFLC) were common between the two irrigation conditions and pleiotropic SNPs were found for chlorogenic and coumaric acids content. The principal components analysis (PCA) and stepwise regression showed that chlorogenic acid, epicatechin in WW and myricetin in DS conditions were the most important components for RSA. The hierarchical cluster analysis (HCA) showed that vanillic acid, myricetin, gallic acid, and catechin were closely associated in both irrigation conditions. Analysis of GWAS showed that 60 candidate genes (CG) were identified of which 18 were involved in stress-induced pathways, phenylpropanoid pathway and flavonoid modifications. Of the CGs, PAL1, CHI, UGT89B1, FLS3, CCR1, and CYP75B137 showed contributed to flavonoid biosynthetic pathways. The results of RNA-seq revealed that the transcript level of PAL, CHI, and CYP75B137 known as early flavonoid biosynthesis related genes and FLS3, CCR1, and UGT89B1 related to the later stages were increased during drought conditions. The transcription factors (TFs) NAC035 and ERF119 related with flavonoids and phenolic acids were up-regulated under drought condition. These findings expand our knowledge of the response mechanisms to drought stress, particularly regarding the regulation of key phenolics biosynthetic genes in rapeseed. Our data also provided specific linked SNPs for marker-assisted selection (MAS) programs and CGs as resources towards realizing metabolomics-associated breeding of rapeseed.